An analysis of information systems security management (issm): the hierarchical organizations vs. emergent organization - Norman, A.A.; Yasin, N.M. (2009)
The adoption of Information Systems (IS) in many businesses is at a fast tempo in order to be more competitive. This fast adoption is very much supported by the rapid technology advancement and the increasing demand from business stakeholders. Together with the introduction of the Internet with its remarkable features, plus the free-form of policing practiced make the Internet more attractive and engaging. The only problem is this attraction has become the magnet for the abuser to misuse the Internet for their profit. This problem has led to many Information Security study to combat threats and protect the business. However, many studies are focus on the technical and engineering solution, where less work were conducted in the IS, management and business issues. In the context of ecommerce, there are very few studies done to understand the problem faced by this subject. Only few e-commerce company manage IS security as the rest believe it is not important. This preliminary paper is written to study the IS security management on the emergent organization environment (e.g. ecommerce) as to the hierarchical organization is dominant in this research field. A framework of analysis is derived to show the contrast of the research objective above.